Perspectives on Sámi participation shaping a duty to consult - Andersson, Anna (2021)
Sweden has a longstanding reputation internationally for promoting and upholding human rights, however leading up to today the state has repeatedly received critique from international human rights bodies for failing to protect Sámi rights. Therefore the state has initiated the process of developing a duty to consult, which could potentially entail a fundamental change for Sámi rights in Sweden.